The Development of Yogurt Powder is High in Minerals, Rich in Antioxidants from Tempeh as a Synbiotic Drink - Nur Amala; Anang M Legowo; Achmad Zulfa Juniarto; Etika Ratna Noer; Ahmad Ni’matullah Al-Baarri (Universitas Aisyah Pringsewu, 2022)
The habit of consuming ultra-processed foods with high calories and low in nutrients increases the prevalence of obesity and mineral deficiencies, such as calcium (Ca), magnesium (Mg), and iron (Fe). The purpose of this study was to determine the content of Ca, Mg, and Fe and antioxidant activity in synbiotic tempeh yogurt powder. This study consisted of three treatments, with the addition of tempeh as much as 0% (YT 0%), 50% (YT 50%), and 95% (YT 95%). The mineral content was analyzed by the permanganometric titration method, while antioxidant activity used the 2,2-diphenyl-1-picrylhidrazyl (DPPH) method. The addition of tempeh in the manufacture of yogurt powder to the content of Ca, Mg, and Fe was significantly different in all treatment groups with a value of (p less than 0.05). The best treatment group with the highest mineral content in YT (0%) and YT (95%) with values of 895.53 + 0.04 and 858.83 + 0.01 mg (Ca), 78.83 + 0.01 and 72.20 + 0.00 mg (Mg) as well as 25.87 + 0.28 and 25.85 + 0.28 mg (Fe) were significantly different from YT (50%). However, the highest antioxidant content in the YT treatment (50%) was 78.12+0.10%. The addition of tempeh in the manufacture of yogurt powder is very significantly different from the value (p less than 0.001) of antioxidant content. The development of yogurt powder high in minerals and rich in antioxidants from tempeh as a synbiotic drink can be an alternative in the management of obesity. Abstrak: Kebiasaan mengkonsumsi makanan ultra-olahan berkalori tinggi dan rendah zat gizi, meningkatkan prevalensi obesitas dan defisiensi mineral, seperti : kalsium (Ca), magnesium (Mg) dan zat besi (Fe) . Tujuan penelitian ini, untuk mengetahui kandungan Ca, Mg, dan Fe dan aktivitas antioksidan dalam bubuk yogurt tempe sinbiotik. Penelitian ini terdiri dari tiga perlakuan, dengan penambahan tempe sebanyak 0% (YT 0%), 50% (YT 50%) dan 95% (YT 95%). Kandungan mineral dianalisis dengan metode titrasi permanganometri, sedangkan aktivitas antioksidan menggunakan metode 2,2-diphenyl-1-picrylhidrazyl (DPPH). Penambahan tempe dalam pembuatan bubuk yogurt terhadap kandungan Ca, Mg, dan Fe secara signifikan beda nyata pada semua kelompok perlakuan dengan nilai (p kurang dari 0,05). Kelompok perlakuan terbaik dengan kandungan mineral tertinggi pada YT (0%) dan YT (95%) dengan nilai 895.53 + 0.04 dan 858.83 + 0.01 mg (Ca), 78.83 + 0.01 dan 72.20 + 0.00 mg (Mg) serta 25.87 + 0.28 dan 25.85 + 0.28 mg(Fe) secara signifikan beda nyata dengan YT (50%). Namun, kandungan antioksidan tertinggi pada perlakuan YT (50%) sebesar 78.12+0.10%. Penambahan tempe dalam pembuatan bubuk yogurt sangat signifikan beda nyata dengan nilai (p kurang dari 0,001) terhadap kandungan antioksidan. Pengembangan bubuk yogurt tinggi mineral dan kaya antioksidan dari tempe sebagai minuman sinbiotik dapat menjadi alternatif dalam manajemen obesitas.